The Effect of Group Investigation and Learning Style on Students’ Writing of Analytical Exposition - Bambang Untoro (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT This study aimed to investigate the influence of group investigation, the difference between auditory and visual students, and the interaction between group investigation and learning style on students’ writing of analytical exposition. It was a quasi-experimental conducted for the second graders of SMA Islam Al-Azhar BSD. The findings revealed that there was an influence of group investigation on students’ writing of analytical exposition. The writing of students that experienced the group investigation model was better than those who had the conventional one. There was a significant difference between auditory students and visual students on their writing of analytical exposition. In both groups, the visual students had better achievement than the auditory ones. However, the visual and auditory students in experimental group had higher improvement. There was also a significant interaction between group investigation and learning style on students’ writing of analytical exposition. It could be concluded that applying a group investigation model was recommended in teaching writing of analytical exposition. ABSTRAK Penelitian ini bertujuan untuk menyelidiki pengaruh model pembelajaran investigasi kelompok, perbedaan antara siswa bergaya belajar audio dan visual, dan interaksi antara model investigasi kelompok dan gaya belajar terhadap kemampuan menulis analytical exposition siswa. Penelitian ini merupakan eksperimen semu yang dilakukan pada siswa kelas XI SMA Islam Al-Azhar BSD. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara siswa yang diajarkan melalui investigasi kelompok dengan siwa yang diajarkan secara konvensional, terdapat perbedaan yang signifikan antara siswa bergaya belajar audio dengan siswa bergaya belajar visual. Siswa visual cenderung berkemampuan menulis lebih bagus daripada siswa audio. Namun, ditinjau dari kedua gaya belajar tersebut, siswa pada kelas eksperimen berkemampuan menulis lebih bagus daripada siswa pada kelompok kontrol. Terdapat interaksi yang signifikan antara investigasi kelompok dan gaya belajar terhadap kemampuan menulis siswa. Hasil penelitian ini menyimpulkan bahwa model pembelajaran investigasi kelompok sesuai untuk pengajaran menulis analytical exposition. How to Cite: Untoro, B. (2016). The Effect of Group Investigation and Learning Style on Students’ Writing of Analytical Exposition. IJEE (Indonesian Journal of English Education), 3(1), 29-45. doi:10.15408/ijee.v3i1.3445 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.3445